FOOTBALL PLAYER TRACKING, TEAM ASSIGNMENT, AND SPEED ESTIMATION USING YOLOV5 AND OPTICAL FLOW - Hartono, Matthew Raymond; Sari, Christy Atika; Ali, Rabei Raad (Informatika, Universitas Jenderal Soedirman, 2025)
Football analysis is indispensable in improving team performance, developing strategy, and assessing the capabilities of players. A powerful system that combines YOLOv5 for object detection with optical flow tracks football players, assigns them to their respective teams, and estimates their speeds accurately. In the most crowded scenarios, the players and the ball are detected by YOLOv5 at 94.8% and 93.7% mAP, respectively. KMeans clustering based on jersey color assigns teams with 92.5% accuracy. Optical flow is estimating the speed with less than 2.3%. The perspective transformation using OpenCV improves trajectory and distance measurement, overcoming the challenges in overlapping players and changing camera angles. Experimental results underlined the system's reliability for capturing player speeds from 3 to 25 km/h and gave insight into the dynamic nature of team possession. However, there is still some challenge: 6% accuracy degradation in high overlap and illuminative changes. The future work involves expanding the dataset for higher robustness and ball tracking, which will comprehensively explain the dynamics of a match. The paper presents a flexible framework for automated football video analysis that paves the way for advanced sports analytics. This would also, in turn, enhance informed decision-making by coaches, analysts, and broadcasters by providing them with actionable metrics during training and competition. The proposed system joins the state-of-the-art YOLOv5 with optical flow and thereby forms the backbone of near-future football analysis.